Pilot study investigating the effect of enteral and parenteral nutrition on the gastrointestinal microbiome post‐allogeneic transplantation. (14th October 2019) - Andersen, Sarah; Staudacher, Heidi; Weber, Nicholas; Kennedy, Glen; Varelias, Antiopi; Banks, Merrilyn; Bauer, Judy
Summary: Nutrition support is frequently required post‐allogeneic haematopoietic progenitor cell transplantation (HPCT); however, the impact of mode of feeding on the gastrointestinal microbiome has not been explored. This study aimed to determine if there is a difference in the microbiome between patients receiving enteral nutrition (EN) and parenteral nutrition (PN) post‐allogeneic HPCT. Twenty‐three patients received either early EN or PN when required. Stool samples were collected at 30 days post‐transplant and analysed with shotgun metagenomic sequencing. There was no difference in microbial diversity between patients who received predominantly EN ( n  = 13) vs. PN ( n  = 10) however patients who received predominantly EN had greater abundance of Faecalibacterium ( P  < 0·001) and ruminococcus E bromii ( P  = 0·026). Patients who had minimal oral intake for a longer duration during provision of nutrition support had a different overall microbial profile ( P  = 0·044), lower microbial diversity ( P  = 0·004) and lower abundance of faecalibacterium prausnitzii_C ( P  = 0·030) and Blautia ( P  = 0·007) compared to patients with greater oral intake. Lower microbial diversity was found in patients who received additional beta lactam antibiotics ( P  = 0·042) or had a longer length of hospital stay ( P  = 0·019). Post‐HPCT oral intake should be encouraged to maintain microbiota diversity and, if nutrition support is required, EN may promote a more optimal microbiota profile.